839 Not Your Everyday Daytime Sleepiness: Two Peas in a Pod. (3rd May 2021) - Stuewe, Elena; Ostrow, Peter; Grover, Aarti; Schumaker, Greg; Oster, Joel; Zacharias, Rajesh
Abstract: Introduction: Obstructive sleep apnea (OSA) and narcolepsy are both causes of excessive daytime sleepiness (EDS). OSA is a more prevalent diagnosis, but it can coexist with narcolepsy and confound diagnosis. We present a case of a delayed diagnosis of type 2 narcolepsy in a patient with known OSA. Report of case(s): A 31-year-old man with depression treated with sertraline and prior history of severe OSA diagnosed at an outside facility presented to our clinic for residual excessive daytime sleepiness. He demonstrated adequate adherence to continuous positive airway pressure (CPAP) of 13 cmH2O over a period of one year, good sleep hygiene and adequate sleep duration. He reported vivid dreams and sleep paralysis in the past, but none recently. There was no history of a delayed sleep phase. He denied hypnagogic or hypnopompic hallucinations or cataplexy. An in-lab polysomnogram (PSG) followed by multiple sleep latency test (MSLT) was ordered for further evaluation. Sertraline was held 2 weeks prior to the study. Overnight PSG on CPAP showed adequate treatment of OSA on CPAP pressures of 13–16 cmH2O. MSLT showed 3/5 sleep-onset rapid eye movement periods with a mean sleep latency of 5.8 minutes. A diagnosis of coexisting type 2 narcolepsy was made. Treatment was initiated with modafinil; however, his symptoms of EDS persisted and he was changed to methylphenidate with subsequent improvement. Conclusion: The case above highlights the importance of maintaining a broad differential when investigating the etiology of EDS. In particular, patients with narcolepsy often experience a significant delay between onset of symptoms and receiving a diagnosis. Diagnosis can be confounded by a lack of classic symptoms and/or the presence of another sleep-related breathing disorder, as in the patient above. Residual EDS can be seen in patients with adequately treated OSA. There is sparse data regarding the co-prevalence of narcolepsy as the etiology of residual EDS in adequately treated OSA. Patients should still be screened for symptoms suggestive of narcolepsy. Persistence of EDS symptoms in young adults with adequately treated OSA should raise suspicion for another sleep-related disorder and merits further investigation. Support (if any):